2010
DOI: 10.1016/j.jaac.2009.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Gray Matter in Attention-Deficit/Hyperactivity Disorder: A Structural Magnetic Resonance Imaging Study

Abstract: ObjectivePrevious studies have shown smaller brain volume and less gray matter in children with attention-deficit/hyperactivity disorder (ADHD). Relatively few morphological studies have examined structures thought to subserve inhibitory control, one of the diagnostic features of ADHD. We examined one such region, the pars opercularis, predicting a thinner cortex of the inferior frontal gyrus (IFG) in children with ADHD.MethodStructural images were obtained from 49 children (24 control; 25 ADHD combined subtyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
91
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(109 citation statements)
references
References 43 publications
11
91
2
5
Order By: Relevance
“…A study by Shaw et al (2006) shows that children with ADHD have cortical thinning throughout the cortex, but particularly in prefrontal regions associated with attention and other executive functions. Other groups have also shown cortical thinning in the frontal regions of individuals with ADHD (Depue et al 2010;McAlonan et al 2007;Batty et al 2010). Depue et al (2010) also showed that disrupted performance in behavioral tasks in ADHD (such as response inhibition, response variability, and processing speed) are associated with reduced volume in the inferior frontal gyrus.…”
Section: Morphologic Changes Measured With Mri In Typical Developmentmentioning
confidence: 96%
“…A study by Shaw et al (2006) shows that children with ADHD have cortical thinning throughout the cortex, but particularly in prefrontal regions associated with attention and other executive functions. Other groups have also shown cortical thinning in the frontal regions of individuals with ADHD (Depue et al 2010;McAlonan et al 2007;Batty et al 2010). Depue et al (2010) also showed that disrupted performance in behavioral tasks in ADHD (such as response inhibition, response variability, and processing speed) are associated with reduced volume in the inferior frontal gyrus.…”
Section: Morphologic Changes Measured With Mri In Typical Developmentmentioning
confidence: 96%
“…By school-age, ADHD is associated with widespread structural brain abnormalities including smaller total cerebral volumes (Friedman and Rapoport, 2015), reductions in total gray matter volumes (Batty et al, 2010), and more localized anomalies in prefrontal and premotor areas (Dirlikov et al, 2015; Mahone et al, 2011b; Shaw et al, 2006), and subcortical structures (Ellison-Wright et al, 2008; Frodl and Skokauskas, 2012; Hoogman et al, 2017; Nakao et al, 2011; Norman et al, 2016). Despite the fairly consistent evidence of frontal lobe anomalies in individuals with ADHD, it is not clear whether these volumetric reductions are secondary to developmental deviations in subcortical regions.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies indicate symptoms of ADHD may be functionally related to reductions in cortical thickness. For example, children with ADHD who performed significantly worse than healthy controls on a Go/No-go inhibition test were found to have reduced cortical thickness of the IFG (Batty et al, 2010). The authors speculated that cortical thinning in the IFG provides more evidence that inhibitory dysfunction in ADHD is due in part to prefrontal cortex abnormalities.…”
mentioning
confidence: 99%